Evaluating and measuring the value, use and impact of digital collections - Hughes, Lorna M. (Facet Publishing, 2012)
"A huge investment has been made in digitizing scholarly and cultural heritage materials through initiatives based in museums, libraries and archives, as well as higher education institutions. The 'Digital Economy' is an important component of institutional planning, and much attention is given to the investment in digital projects and programmes. However, few initiatives have examined the actual use, value and impact of digital collections, and the role of digital collections in the changing information environment. As the creative, cultural and educational sector faces a period of restricted funding, it is timely to re-examine the use of the digital collections that have been created in the past twenty years, and to consider their value to the institutions that host them and to the communities of users they serve"--Publisher.